Modelling The Transmission Of Tuberculosis In Closed Space Using Microscopic Pedestrian Simulation - Sabri, Nor Shamira (2023)
Due to the infamous COVID-19 pandemic, Tuberculosis deaths are rising for the first time in more than a decade. Tuberculosis is the second (after COVID-19) deadliest infectious killer that has been exists in this world for centuries. Despite the availability of adequate vaccination, it is still roamed around the world and became one of the leading diseases that contribute significantly to the world’s mortality rate. Therefore, this works aims to simulate how this infectious disease spread by utilizing the Susceptible-Infected (SI) model. As the research progresses, it is found that the general epidemiological studies that uses compartmental method ignore the heterogeneous of social interaction between humans. Thus, this research has proposed the integration of the Social Force model with the SI approach to imitate realistic human interaction while capturing the pathogen transmission process from one person to another. This work aims to simulate the movement and interaction between infected person and another susceptible person in a closed space when an infectious disease is present and develop with a process-oriented methodology framework following this setting set in the research. The methodological framework proposed is divided into three major stages: problem characterization, model construction also model analysis and evaluation, which work as step-by-step processes to achieve the objective sets.